PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Greatson Paul Hutapea; Romulo Sinabutar (Jurnal Ekonomis, 2021)
This study aims to determine the effect of company profitability and solvency on audit report lag. Food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2018 period became the population in this study. The sample used in this study was selected by purposive sampling. From the results of the sample criteria that have been determined from 34 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX), 16 companies were eliminated because these companies did not publish their financial reports during 2016-2018 period, and only 18 companies still meet the criteria. To determine the effect of the independent variable on the dependent variable, the t test and F test were carried out with a significance level (α) of 0,05 or 5%. The data analysis method in this research is multiple linear regression. The results showed that profitability (ROE) had no significant effect on audit report lag 0.089>0.05 with t count 1.733, and solvency (DER) had a significant effect on audit report lag 0.000<0.05 with t count 7.404. And profitability and solvency simultaneously affect the audit report lag 0.000<0.05 with F count 27.872.